2015
DOI: 10.1590/0104-1169.0660.2657
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic and clinical variables with the state of frailty among older inpatients

Abstract: Objectives: to identify the prevalence of frailty among inpatient older adults in a clinical hospital and check the association of the socioeconomic and clinical characteristics with the state of frailty. Method: observational, cross-sectional and analytical study, conducted with 255 hospitalized patients. Materials used: structured instrument for the economical and clinical data and frailty phenotype of Fried. Descriptive and bivariate statistical analysis was carried out and, by means of chi-square tests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
8
0
4
Order By: Relevance
“…Among frail participants, the median LOS was 10 (IQR: 7-14) days, compared with 8 (5-12) days in prefrail participants and 7 (5)(6)(7)(8)(9)(10)(11) days in robust participants. The results of the multilevel negative binomial regression model showed that frailty and pre-frailty increased the length of hospitalization (frailty: β = 0.176, 95% CI: 0.136-0.216, and p < 0.001; pre-frailty: β = 0.095, 95% CI 0.066-0.124, and p < 0.001).…”
Section: Frailty and Length Of Hospitalizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Among frail participants, the median LOS was 10 (IQR: 7-14) days, compared with 8 (5-12) days in prefrail participants and 7 (5)(6)(7)(8)(9)(10)(11) days in robust participants. The results of the multilevel negative binomial regression model showed that frailty and pre-frailty increased the length of hospitalization (frailty: β = 0.176, 95% CI: 0.136-0.216, and p < 0.001; pre-frailty: β = 0.095, 95% CI 0.066-0.124, and p < 0.001).…”
Section: Frailty and Length Of Hospitalizationmentioning
confidence: 95%
“…Frailty has gained increasing attention as it is by far the most prevalent geriatric condition amongst older patients that heavily impacts chronic health status. The estimated prevalence rates of frailty in community-dwelling older people are 2.6-19.6% [5][6][7] and range from 25.2 to 48.8% in hospitals [8][9][10][11][12]. The variation in percentage reflects the difference in the sampled population and the criteria for assessing frailty [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…Enferm. UFSM, Santa Maria, v11, e8: p. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]2021 No que concerne à hospitalização, distintas dificuldades e desafios são enfrentados pela equipe de enfermagem no cuidado à pessoa idosa, visto que a identificação das necessidades de cuidado recai às características peculiares da senescência e diminuição da capacidade funcional para além da condição de agravo. 2 Isso exige conhecimentos e habilidades dos profissionais de enfermagem, de modo que atendam às particularidades das pessoas idosas e as questões inerentes ao processo de envelhecimento.…”
Section: Introdução Introdução Introdução Introduçãounclassified
“…Resultado convergente foi encontrado em estudo realizado com pessoas idosas internadas em hospital de Uberaba, Minas Gerias, no qual a média de idade foi de 68,68 anos, sendo a maioria na faixa etária de 60 a 70 anos. 11 Em relação à escolaridade, verificou-se que a metade das pessoas idosas estudou de 4 a 7 anos e não concluiu o ensino fundamental, dado semelhante ao perfil de idosos do RS. 12 Ante essa variável, importa conhecer a escolaridade para planejar os cuidados, visto que a educação pode interferir na percepção de saúde/doença, cuidado e autocuidado.…”
Section: Introdução Introdução Introdução Introduçãounclassified
See 1 more Smart Citation